Operational Challenges and Achievements in 18F-Fluorodeoxyglucose Production during the Pre-automation Phase of Cyclotron at NINMAS - Mia, Md Shohag; Mehdi, Hasan; Biswasarma, Sanchoy Chandra; Siddiquee, Nur E Alam; Islam, Sanjida; Kadir, Muhtasim; Uddin, Md Jashim; Azim, Mohammad Anwar Ul; Hossain, Md Nahid; Begum, Ferdoushi (Bangladesh Journal of Nuclear Medicine, 2025)
An important step forward for nuclear medicine in Bangladesh was the establishment of the 18/9 MeV Cyclotron (Model: Cyclone 18/9, IBA) at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) under the Bangladesh Atomic Energy Commission (BAEC). This cyclotron, capable of operating at 18 MeV for protons and 9 MeV for deuterons, has been pivotal in producing 18F, a crucial radioisotope for PET imaging. During the pre-automation phase, the cyclotron supported limited 18F production, addressing the initial demand for 18F-FDG and significantly reducing patient waiting times for PET scans in Dhaka. Initially, 18F production was performed with a low beam current of 10–12 μA, yielding a modest amount of radioisotope transferred for synthesis. Despite the limitations of manual operations, nearly 10 batches of 18F-FDG were successfully produced during this phase. The transition to automation allowed the cyclotron to operate at its full capacity, with beam currents increased to 40–50 μA. This enhancement enabled the production of 18F within a 60-120 minute bombardment period, meeting the growing demand for PET imaging. This paper highlights the operational challenges encountered during the pre-automation period, including low production efficiency and manual handling constraints. Key factors influencing 18F production, such as beam current, irradiation time, enriched 18O water quantity, Dee voltage, vacuum levels, and other parameters, were carefully studied to optimize yield. The pre-automation phase provided valuable insights into cyclotron operation, laying the groundwork for current automated processes that have greatly enhanced production efficiency and reduced operational costs. This study is a testament to the innovative efforts that bridged the gap between manual and automated 18F production, ensuring the availability of radiopharmaceuticals in Bangladesh. Bangladesh J. Nuclear Med. 28(1): 119-124, 2025